Two Novel Compound Heterozygous ADGRG1/GPR56 Mutations Associated with Diffuse Cerebral Polymicrogyria - Jha, Ruchika; Kovilapu, Uday B.; Devgan, Amit; Sondhi, Vishal (Journal of Pediatric Genetics, 2020)
Background Polymicrogyria (PMG) has environmental or genetic etiologies. We report a 8-year-old boy with diffuse PMG and two novel adhesion G protein-coupled receptor G1 (ADGRG1)/G protein-coupled receptor 56 (GPR56) mutations.Case Report The proband has intellectual disability, spastic quadriparesis, and intractable epilepsy without antenatal or perinatal insults. Brain magnetic resonance imaging revealed PMG involving fronto-polar, parietal and occipital lobes with decreasing antero-posterior gradient, and a thinned-out brain stem. Targeted exome sequencing identified two novel compound heterozygote ADGRG1/GPR56 mutations (c.C209T and c.1010dupT), and each parent carries one of these mutations. Subsequent pregnancy was terminated because the fetus had the same mutations.Conclusion The detected mutations expanded the genetic etiology of PMG and helped the family to avoid another child with this devastating condition.
Keywords: drug resistant epilepsy; intellectual disability; cortical malformations